Recent finds ascribed to the Middle Bronze Age at Piatra Şoimului (Neamţ County) - Diaconu, Vasile; Mischka, Doris; Mischka, Carsten (Memoria Antiquitatis – Arheologie, 2025)
Sixty-five years after the initial research conducted at the eponymous site of the Costișa culture, our understanding of this Bronze Age entity has advanced significantly, but each discovery has the potential to refine the broader picture known today. The Piatra Șoimului site, located in the Carpathian area of Neamț County, is renowned for Eneolithic and ancient discoveries (dacians) and is among the few where Costișa culture remains were identified long before the culture was formally defined. Excavations carried out in the 1930s and 1970s uncovered a range of Bronze Age remains, though much of this material is still unpublished. Recent field surveys combined with geophysical investigations conducted by a team from the „Friedrich-Alexander” University of Erlangen-Nürnberg (Germany) have enabled the identification of new Middle Bronze Age materials and provided data on the density and spatial dynamics of these remains. This article aims to analyse and interpret the pottery materials predominantly attributed to the Costișa culture by applying technological, typological, quantitative,spatial criteria. In addition to the pottery from this cultural context, a few fragments displaying Monteoru cultural traits were documented; these findings are consistent with other sites in the adjacent geographical area. Last but not least, recent Bronze Age discoveries have been discussed in a broader context by reprising additional information regarding previously discovered metal artefacts near the Piatra Șoimului site. <br
Keywords: Middle Bronze Age; Costișa culture; Piatra Șoimului; pottery; geophysical investigations; spatial analysis